Colpocephaly in a 62-Year-Old Woman: A Case Report - Edzie, Emmanuel Kobina Mesi; Dzefi-Tettey, Klenam; Gorleku, Philip Narteh; Kusodzi, Henry; Asemah, Abdul Raman (Archives of Clinical and Medical Case Reports, 2020)
Colpocephaly is the disproportionate dilation of the occipital horns of the lateral ventricles and commonly diagnosed in infancy, but very rare in adults. We report a case of a 62-year old known hypertensive woman with a predominantly left sided colpocephaly which was incidentally diagnosed during a Computed Tomography (CT) Scan examination at the Cape Coast Teaching Hospital after admission with a history of palpitation, chest pains, and generalized bodily pains. She was found to be slightly confused with all other examination findings being normal except a blood pressure of 170/101 mmHg. A provisional diagnosis of acute confusional state secondary to uncontrolled hypertension was made, to rule out electrolyte imbalance and cerebrovascular accident, the investigation of which revealed this case of colpocephaly in an adult. Colpocephaly in adults is rare and often asymptomatic, therefore may be misdiagnosed as normal pressure hydrocephalus and an awareness of this will help prevent unnecessary diagnostic and therapeutic interventions.